EMPIRICAL ANALYSIS OF BASEL III EFFECTS IN INTEREST RATE ON THE KOSOVO BANKING SYSTEM - Ereza Arifi; Esat Durguti; Qazim Tmava; Nexhat Kryeziu (European Scientific Journal, ESJ, 2014)
The purpose of this working paper is to investigate effects of potential implementation of Basel III on an average interest rate of loans in banking system of Kosovo by using times series data aggregating for all commercial banks in the period from 2006 to 2013, in quarterly basis. The study used quantitative and qualitative research approach and is analyzed by using linear regression model for average interest rate on loans. Linear regression model was applied to investigate the new requirements of Basel III framework for the banks and their effects on average interest rate on loans. To investigate new requirements of Basel III and its impact on average interest rate of loans we use in our analysis capital adequacy ratio (quick ratio), management efficiency ratio, asset quality ratio, liquidity ratio, investment to asset ratio, loans to asset ratio and deposits to asset ratio. The results of regression model summary statistics for average interest rate on loans shows that interest rate of loans has a strong correlation with explanatory variables that we used in our model, that explanatory variables explain 76.5 percent of dependent variable and we can conclude that a model is a proper and fit. The empirical result shows that the ratio that we mentioned above has a significant influence on the average interest rate on loans in the Kosovo Banking System.